Faktor Stabilitas Balok Kayu pada Konfigurasi Pembebanan Terpusat: Stability Factor of Wooden Beams in One Point Loading - Agustina Hayatunnufus; Naresworo Nugroho; Bahtiar, Effendi Tri (Jurnal Teknik Sipil dan Lingkungan, 2022)
The use of wood as a building material must be designed quite rigid and strong. According to SNI 7973:2013, the corrected design value on the wooden structure components must be in accordance with the condition of wood to be used. The objective of this study is to determine the value of timber beams stability (CL) both of softwood and hardwood based on SNI 7973:2013 for construction purposes. The material in this research to be used are pine (Pinus merkusii), agathis (Agathis dammara), mahagony (Swietenia macrophylla), and red meranti (Shorea leprosula). Testing of physical properties include moisture content, specific gravity, and density, meanwhile testing of mechanical properties include flexural strength, modulus of elasticity, and ductility. Mechanical testing is carried out on a small clear specimens and full-size specimens, while the physical properties are tested only on a small clear specimens. The full-size specimens are visually sorted and the strength ratio (S) is determined prior to mechanical testing. The result of this study showed that the highest strength ratio was in meranti 55.85%, agathis 52.98%, pine 46.76%, and mahogany 46.60%. Softwood has a lower S value to more knot defects than hardwood. The slenderness ratios of agathis, pine, mahogany, and meranti wood respectively are 7.48, 7.45, 7.40 and 7.66 so that all specimens are referred to as short beams. The value of beam stability (CL) is close to 1 that indicates that the beams are stable and does not twist.